IMPROVEMENT OF STUDENT LEARNING OUTCOMES THROUGH TEACHING MATERIALS AIDED BY SCIENCE COMICS GLOBAL WARMING - Nur Tatimmatus Solihah; Siti Nurul Hidayati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This research aimed to describe the improvement of junior high school student learning outcomes through teaching materials aided by science comics on global warming materials. This research used a One-Group Pretest-Posttest Design research method. The results of research conducted in class VII-B SMP Negeri 2 Buduran in the form of student learning outcomes obtained before and after learning and analyzed the increase based on n-gain results. As many as 81% of students get n-gain in the medium category and 19% of students get n-gain in the high category with average n-gain obtained that is equal 0.60 which belongs to the medium category. Based on the results of these studies, it can be concluded that through teaching materials assisted by science comics can improve junior high school student learning outcomes. Keywords: teaching materials, comics science, learning outcomes.